METHODOLOGY FOR DEVELOPING LANGUAGE AND FUNCTIONAL LITERACY THROUGH DIGITAL TECHNOLOGIES (Ideal Journal of Multidisciplinary Research, 2026)
This article explores the theoretical and practical foundations of developing functional literacy through digital technologies. It analyzes the role of information and communication technologies in modern education, particularly their contribution to enhancing students’ independent thinking, problem-solving abilities, and real-life skills. Additionally, methodological recommendations for the effective use of digital tools in the educational process are presented. One of the key challenges facing today’s education system is preparing learners for real-life situations by fostering critical thinking, information analysis, and sound decision-making skills.
Keywords: Functional literacy, digital technologies, competence, interactive methods, information technologies, educational efficiency, innovation.